Advances in capillary electrophoresis-mass spectrometry for pharmaceutical analysis - N. Udayakumar, (Asian Journal of Pharmaceutics (AJP), 2025)
Capillary electrophoresis-mass spectrometry (CE-MS) combines the high separation efficiency of capillary electrophoresis with the exceptional sensitivity and specificity of mass spectrometry. CE-MS has gained significant traction in pharmaceutical analysis, offering unique advantages in the analysis of pharmaceuticals, biologics, and their metabolites. Recent technological advancements have enhanced CE-MS applicability, addressing historical challenges in interface design and improving system robustness and sensitivity. Novel capillary coatings and background electrolytes have expanded the range of analyzable compounds. CE-MS is utilized across various stages of drug development and quality control, proving valuable in small-molecule drug analysis, and offering highresolution separations of structural isomers and chiral compounds. In biopharmaceuticals, CE-MS has emerged as a powerful tool for characterizing complex protein therapeutics, including monoclonal antibodies and biosimilars. The technique provides detailed information on post-translational modifications and higher-order structures, ensuring biologic drug quality and safety. CE-MS has shown potential in metabolomics, contributing to drug metabolism understanding and biomarker discovery. The technique’s minimal sample and solvent requirements align with green analytical chemistry principles. Ongoing research focuses on improving sensitivity, throughput, and data analysis capabilities. Integration with other analytical techniques and advancements in bioinformatics tools are enhancing CE-MS applications in pharmaceutical analysis, particularly in the era of personalized medicine and biologics.